Modelling copper emissions from antifouling paints applied on leisure boats into German water bodies. (15th November 2021) - Morling, Karoline; Fuchs, Stephan
Abstract: Copper-containing antifouling paints (AFP) are widely used for leisure boat maintenance. Cu emitted from AFP into German surface water bodies has been suggested to be a significant source of heavy metal pollution, threatening water quality. We developed two scenarios to model Cu emissions from AFP applied on leisure boats on national scale, which allow identifying regional hotspots. The top-down approach (scenario A) was based on a previous study on national AFP consumption, while in the bottom-up approach (scenario B), median and interquartile range of Cu release rates depending on salinity conditions were considered for emission estimation. Both scenarios clearly highlighted the locally high emission pressure on inland waters in popular watersport regions, identifying these as requiring intense protection. Scenario B generally predicted lower Cu emissions (sea: 11.05–25.53 t a −1, inland: 14.15–34.59 t a −1 ) than scenario A (sea: 22.53 t a −1, inland: 47.97 t a −1 ). To evaluate their relevance, scenario results were compared to emissions modelled with MoRE (Modelling of Regionalized Emissions), which is used as reporting tool on substance emissions by Germany. According to scenarios A and B, the emission from AFP accounted for 13 % and 4–9 % of the total Cu emissions into inland waters in 2016, respectively. Scenario results were similar or higher than other emission pathways such as industrial direct dischargers. Thus, we consider Cu emissions from AFP as a significant pathway to be included in the MoRE emission inventory. We recommend scenario B for implementation as it allows a more flexible adaptation for future modelling. Graphical abstract: Image 1 Highlights: Modelling Cu emissions from leisure boat antifouling paints (AFP) on national scale. Accounting for influence of salinity on Cu release rates from AFP. Identifying hotspots of Cu pollution from AFP use and vulnerable regions. Cu release from AFP comparable to and may exceed other emission pathways.